Pergeseran Tindak Kesantunan Direktif Siswa Dalam Menyapa Guru Di Sekolah Menengah Pertama Berlatar Belakang Budaya Jawa - Karlena, Lilis, Prof. Dr. Harun Joko Prayitno, M.Hum (2017)
This study aims to describe the shifting and functioning forms of politeness directive of students in greeting in junior high school with a Javanese cultural background. Describes the pragmatic power contained in Tindak Kesantunan Direktif (TKD). This research cans also application in teaching materials in SMP. The method used in the provision of data is, with refer technique, recording techniques, and record techniques. Data analysis used referral and translational method. The result of this research is 30 speeches, 20 forms of speech acts that are found in the speech of the students greet teachers in junior high school with Javanese cultural background. Shift form of TKD 16 date and function of TDK there are 14 date. The pragmatic power contained in TDK consist of, (1) notifying, (2) saying thank you, (3) saying goodbye, (4) inquire, (5) borrowing something, (6) request, (7) insinuating, (8) suggesting , And (9) pay. Implementation as teaching materials SMP on basic competence 10.2 Bringing the event with good and correct language, and polite. Indicators that must be achieved, bring able to the event with a communicative language.